KESADARAN HUKUM MAHASISWA UNIVERSITAS MERCU BUANA JAKARTA TERHADAP UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Andi Setiawan (POLITEKNIK LP3I JAKARTA, 2018)
AbstractThe dishonesty of business leaders in marketing their products and services in Indonesia often harms consumers. Losses suffered include material, physical, psychological and mental. Expectation to suppress the high number of fraud cases of business leaders against consumers came after the government published a consumer protection law. Although Law No. 8 of 1999 concerning Consumer Protection was enacted almost two decades ago, there are still many consumers who are harmed by the mischievous conduct of business leaders. Legal awareness indicators of Mercu Buana University students in Jakarta on Law No. 8 of 1999 concerning Consumer Protection are in the sufficient category. The campus also equips students with Business Law courses. This illustrates that they are critical and thorough students before consuming a product / service. They are able to protect their own interest and those around them in buying and choosing a product and service so that they are able to avoid fraud by business leaders. They are also able to take the necessary steps if the fraud occurs to them.Keywords: Legal awareness, Consumer Protection, Law number 8 / 1999 Students